2010
DOI: 10.3233/jvr-2010-0495
|View full text |Cite
|
Sign up to set email alerts
|

Closures are the tip of the iceberg: Exploring the variation in state vocational rehabilitation program exits after service receipt

Abstract: Despite the important role that state vocational rehabilitation (VR) agencies play in promoting employment for people with disabilities, little is known about how their exits after service receipt vary with individual characteristics and across states compared to the general population with disabilities. We used fiscal year 2007 RSA administrative data and American Community Survey public use files to calculate the ratio of the number of individuals exiting VR after service receipt to the estimated number of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
(14 reference statements)
2
11
0
Order By: Relevance
“…Chan and colleagues (2016), found that gender (favoring males) was a significant predictor of a successful closure. This finding has also been supported in previous research indicating that male closure rates outnumbered female closure rates by 17% (Stapleton et al, 2010). However, Dutta and colleagues (2008) found gender to be an insignificant variable when investigating the closure patterns of VR agencies.…”
Section: Personal Characteristicssupporting
confidence: 75%
See 4 more Smart Citations
“…Chan and colleagues (2016), found that gender (favoring males) was a significant predictor of a successful closure. This finding has also been supported in previous research indicating that male closure rates outnumbered female closure rates by 17% (Stapleton et al, 2010). However, Dutta and colleagues (2008) found gender to be an insignificant variable when investigating the closure patterns of VR agencies.…”
Section: Personal Characteristicssupporting
confidence: 75%
“…Even with the over 60% of competitive employment rates achieved by individuals with disabilities who receive VR services, research is still limited regarding the factors that impact the closure rates between VR agencies across the 50 states. Previous research has shown that state VR agencies differ in their reported closure rates for successful job placements (Stapleton, Honeycutt, & Schechter, 2010). However, there is scant literature about what may be contributing to these variations in closure rates.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations